Studi Literatur: Peningkatan Kemampuan Berpikir Kritis Siswa Sekolah Dasar pada Pembelajaran IPS Melalui Komik Digital - Hayati, Firda; Nur As'syifa, Rattu Anggun; Farhurohman, Oman (IBTIDA-Jurnal Kajian Pendidikan Dasar, 2024)
Social Sciences (IPS) is identified as one of the other subjects taught from elementary to higher education. Revealing various events, facts, ideas and generalizations related to social problems. In the process of learning IPS in general, students only write material so that students do not use their critical thinking skills. The purpose of this study is to determine the effect of the use of digital comics on students' critical thinking skills in IPS learning. The method used in this study is a literature study, namely reviewing several sources such as the internet and Google Scholar that are in accordance with the topics used. Researchers analyzed journals or articles related to digital comics and critical skills totaling 4 articles. Where the article was published no more than the last 10 years. The results of the study showed that the use of digital comics can improve students' critical thinking skills and digital comics are very suitable for use to support education. In addition to being easy to carry, digital comics can also be used simultaneously or independently, and learning becomes more practical and effective. similar to research conducted by Novia Ramadhani, et al. entitled Development of Digital Comic Learning Media on Critical Thinking Skills of Fifth Grade Students in Thematic Learning that after conducting a validity test, it showed that there was an impact produced by the use of digital comics on the critical thinking skills of fifth grade students when learning about thematic topics.